Mapping study: Analysis of the Riau vision 2025 research - Syed agung Afandi; Muslim Afandi; Rizki Erdayani; Reski Lestari (International Journal on Social Science, Economics and Art, 2023)
This study aims to map out the study of Malay culture in accordance with the Riau Government's 2025 vision. This study employs a qualitative methodology and a literature review methodology. From January 2005 to February 2021, 228 articles on the Garuda Indonesia Publication Index Portal contained the keywords Riau Malay, according to the findings of this study. The articles are organized into the following five categories: cultural issues (42%), education issues (27%), political issues (16%), socio-economic issues (11%), and religious issues (4%). Malay culture is one of the supporting pillars of national culture. To prevent the polarization of Riau Malay Culture, the Riau Malay community has established synergistic traditional areas to preserve their culture. Islam's introduction to Riau has resulted in the transformation of Malay culture. Islam has had a significant impact on the Riau Malay community's culture, politics, education, religion, and socio–economics.